Energy Economics in Islamic Countries: A Bibliometric Review - Laila, Nisful; Rusydiana, Aam S.; Irfany, Muhamad Iqbal; HR, Imron; Srisusilawati, Popon; Taqi, Muhamad (International Journal of Energy Economics and Policy, 2021)
Energy has an important role in the economic growth of a country, the more energy a country has, the better the country's economy. This study tries to map the development of research published in the field of energy economics. The research was conducted using VOSViewer software. The data analyzed were in the form of scientific research related to energy economics in Islamic countries as many as 45 articles published in the last 10 years. The results showed that the number of publications on the development of research results in the field of energy economics continued to increase, with various research methods and countries of study objects. The network visualization shows that the energy economy research development map is divided into 5 clusters. Cluster 1 consists of 7 keywords, cluster 2 consists of 7 keywords, cluster 3 consists of 5 keywords, cluster 4 consists of 5 keywords and cluster 5 consists of 2 keywords. It was found that the most familiar keywords are Country, Renewable Energy, CO2 Emission. Other findings based on the results of text mining are the analysis of Kaya Identity in Islamic countries and solutions in the form of sustainable energy use. Keywords: Energy Economics, Kaya Identity, Bibliometrics. JEL Classifications: Q40, Q43, Q56 DOI: https://doi.org/10.32479/ijeep.10763